2019
DOI: 10.1002/bit.26961
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional microfluidic tumor–macrophage system for breast cancer cell invasion

Abstract: The recrudescence of breast cancer can partly be attributed to poor understanding of the early steps and the mechanisms involved in breast cancer metastasis, especially how tumor inflammatory cells including tumor-associated macrophages (TAM) affect invasion process. However, invasion-related biological studies in traditional in vitro assays or in vivo models are challenging due to the arduousness in establishing models that precisely reproduce the tumor invasion environment. To this end, we proposed a juxtapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
(34 reference statements)
1
28
0
Order By: Relevance
“…[2] In this study, the combination of a generator with microchambers and pneumatic components (i.e., PμSs) permits active/parallel heterotypic 3D tumor manipulation and parallel/mutually independent tumor investigation in a single microfluidic device, which was hardly achieved using the reported microdevices applied to produce gradients of anti-cancer pharmaceutical compounds. [41][42][43] Thus, these results confirmed that the established microfluidic system was able to carry out robust chemical gradient production, which is useful for performing parallel chemotherapy assessment, antitumor analysis and drug screening in a single device.…”
Section: Microfluidic Chemical Gradient Productionsupporting
confidence: 65%
“…[2] In this study, the combination of a generator with microchambers and pneumatic components (i.e., PμSs) permits active/parallel heterotypic 3D tumor manipulation and parallel/mutually independent tumor investigation in a single microfluidic device, which was hardly achieved using the reported microdevices applied to produce gradients of anti-cancer pharmaceutical compounds. [41][42][43] Thus, these results confirmed that the established microfluidic system was able to carry out robust chemical gradient production, which is useful for performing parallel chemotherapy assessment, antitumor analysis and drug screening in a single device.…”
Section: Microfluidic Chemical Gradient Productionsupporting
confidence: 65%
“…A decrease in the extravasation efficiency of TNBCs was shown due to the presence of paracrine signals, corresponding with an anti-metastatic role of monocytes ( Figure 4A ; Boussommier-Calleja et al, 2019 ). In contrast, Mi et al (2019) created an invasion system with two compartmentalized gel channels: one seeded with MBA-MD-231 cells, and the other with macrophages and an endothelial barrier ( Figure 4B ). In their model, TNBC cells in contact with TAMs led to an invasive phenotype, as demonstrated by increased survival of tumor cells following paclitaxel treatment.…”
Section: Toward Tissue-specific Breast Cancer Modelsmentioning
confidence: 99%
“…Scale bars are 500 mm. Figures are adapted from Mi et al (2019) . (C) Example of on-chip TME partial-confinement for examining TNBCs.…”
Section: Toward Tissue-specific Breast Cancer Modelsmentioning
confidence: 99%
“…It was shown that spheroids of primary lung adenocarcinoma epithelial tumor cells co-cultured with primary pericytes are less responsive to cisplatin perfusion than PLETCs monoculture (Ruppen et al, 2015) Different non-malignant cell types exert different effects on cancerous cells in 3D microfluidic co-cultures. Mi and colleagues showed that tumor-associated macrophages and monocytes contribute more to the survival of breast carcinoma cell lines in response to paclitaxel treatment in the microfluidic device when compared to epithelial cells (Mi et al, 2019).…”
Section: Drug Screening In Microfluidic-based 3d Co-culturesmentioning
confidence: 99%